Outcomes of patients with heart failure after primary prevention ICD unit generator replacement. Issue 1 (28th February 2019) - Looi, Khang-Li; Gavin, Andrew; Cooper, Lisa; Dawson, Liane; Slipper, Debbie; Lever, Nigel
Abstract : Objective: Data describing outcomes after implantable cardioverter-defibrillator (ICD) unit generator replacement in patients with heart failure (HF) with primary prevention devices are limited. Method: Data on patients with HF who underwent primary prevention ICD/cardiac resynchronisation therapy-defibrillator (CRT-D) implantation from 2007 until mid-2015 who subsequently received unit generator replacement were analysed. Outcomes assessed were mortality, appropriate ICD therapy and shock, and procedural complications. Results: 61 of 385 patients with HF with primary prevention ICD/CRT-D undergoing unit generator replacement were identified. Follow-up period was 1.8±1.5 years after replacement. 43 (70.5%) patients had not received prior appropriate ICD therapy prior to unit replacement. The cumulative risks of appropriate ICD therapy at 1, 3 and 5 years after unit replacement in those without prior ICD therapy were 0%, 6.2% and 50% compared with 6.2%, 59.8% and 86.6%, respectively (p=0.005) in those with prior ICD therapies. No predictive factors associated with appropriate ICD therapy after replacement could be identified. 41 (32.8%) patients no longer met guideline indications at the time of unit replacement but risks of subsequent appropriate ICD interventions were not different compared with those who continued to meet primary prevention ICD indications. The 5-year mortality risk after unit replacement was 18.4% and there were high procedural complication rates (9.8%). Conclusion: No predictive marker successfully stratified patients no longer needing ICD support prospectively. Finding such a marker is important in decision-making about device replacement particularly given the concerns about the complication rates. These factors should be considered at the time of ICD unit replacement.